Overeducation: dynamics, wounds and scars - Santos, Vítor Gabriel Pereira (2021)
The present study investigates the extent to which the e ects of entering the la- bor market in overeducated positions pertrain throughout workers careers. Adopting a time-to-event modeling approach, we analyze overeducation persistency and evaluate the existence of state duration dependence. We further investigate future earnings e ects associated with past overeducation employment. Our results report strong entrapment e ects rising from overeducation and for overeducated workers to yield lower returns for their schooling investment than their equally matched peers. We also conclude the e ects of overeducation to perpetuate to future job allocations, with workers having an overeducation employment background reported as su ering wage losses ranging from 3.5% to 14%.